Scintillation primary quenching in organic condensed media revisited - Galunov, N.Z.; Martynenko, E.V.; Semynozhenko, V.P.; Tarasenko, O.A. (Functional Materials, 2009)
The revised model of the scintillation process in organic condensed media takes into account the fundamental influence of the polarization effects on the processes proceeding in a track of ionizing particle. A very fast process of the primary quenching of the hot polaron pairs is the first "step" of "specific quenching". It defines the future processes of formation both fast and slow components of a scintillation pulse. The secondary quenching is the second "step" of "specific quenching". It takes place after track formation and thermalization. It results in decrease of the number of charge states and excited molecules. The influence of the primary quenching on "specific quenching" process is much stronger than the influence of the secondary quenching. Уточнена модель сцинтиляційного процесу в органічних конденсованих середовищах враховує визначальний вплив поляризаційних ефектів, що відбуваються у треку іонізуючої частинки. Дуже швидкий процес первинного гасіння гарячих поляронних пар - це перший "етап" "специфічного гасіння". Він визначає наступні процеси формування як швидкої, так і повільної компонент сцинтиляційного імпульсу. Вторинне гасіння є другим "етапом" "специфічного гасіння". Цей процес протікає після формування та термалізації треку. Вплив первинного гасіння на "специфічне гасіння" набагато сильніше, ніж вплив вторинного гасіння. Уточненная модель сцинтилляционного процесса в органических конденсированных средах учитывает определяющее влияние поляризационных эффектов, протекающих в треке ионизирующей частицы. Очень быстрый процесс первичного тушения горячих поляронных пар - это первый "этап" "специфического тушения". Он определяет последующие процессы формирования как быстрой, так и медленной компонент сцинтилляционного импульса. Вторичное тушение является вторым "этапом" "специфического тушения". Этот процесс протекает после формирования и термализации трека. Влияние первичного тушения на "специфическое тушение" гораздо сильнее, чем влияние вторичного тушения.